Branded - Beukes, Lauren (Department of English Language and Literature, 2014)
Branded is set in an allegorical near future South Africa stratified by an economic apartheid. Cell phones are used for social control, both as passes that provide entry to designated places and electroshock punishment that can be administered by the SAPS. In the wake of a superdemic, crime and anti-corporate activism are harshly dealt with and the worst punishment is being 'disconnected', your cell phone deactivated, cut off from money, communication and entrance to public spaces. Genetic tampering has become pervasive with mutacute pets and modified police dogs called Aitos. The story follows four characters: Kendra, a young artist who has just enrolled in a flagship corporate sponsorship programme, Toby, a waster who dabbles in journalism, Lerato, an ambitious Aidsbaby raised in a corporate skills institute and desperate to defect to another company and Tendeka, an anti-corporate activist who is becoming increasingly rabid.